Mixed-Dimensional In-Plane Heterostructures from 1D Mo6Te6 and 2D MoTe2 Synthesized by Te-Flux-Controlled Chemical Vapor Deposition - Kim, Hyeonkyeong; Johns, James E.; Yoo, Youngdong (Small, 2020)
Mixed-dimensional van der Waals heterostructures are scientifically important and practically useful because of their interesting exotic properties resulting from their novel hybrid structures. This study reports the composition- and phase-selective fabrication of low-dimensional molybdenum/tellurium (Mo/Te) compounds and the direct synthesis of mixed-dimensional in-plane 1D–2D Mo6Te6–MoTe2 heterostructures. The composition and phase of the Mo/Te compounds are controlled by changing the Te atomic flux that is adjusted by the Te temperature. Metallic 1D Mo6Te6 wires with an intrinsic 1D structure with a diameter of 3–8 nm and length of 100–300 nm are synthesized to form wire networks under low Te flux conditions, whereas the semiconducting few-layer 2H MoTe2 films preferentially oriented along the <0001> direction are obtained under high Te flux. Under medium Te flux, the mixed-dimensional in-plane 1D–2D Mo6Te6–MoTe2 heterostructures are synthesized in which the semiconducting few-layer 2H MoTe2 circular domains are edge-contacted by the metallic 1D Mo6Te6 wire networks. Furthermore, the present Te-flux-controlled method reveals that the 1D Mo6Te6 networks change to few-layer MoTe2 films as the Te flux increases. The in-plane 1D–2D Mo6Te6–MoTe2 heterostructures synthesized by this method can be considered as advanced edge-contacted 2D semiconductors for high-performance 2D electronics.
Keywords: 1-D structures; Circular domains; Direct synthesis; Exotic properties; Flux conditions; Flux-controlled; Hybrid structure; Low dimensional; 1D–2D heterostructures; in-plane metal–semiconductor; mixed-dimensional heterostructures; Mo 6Te 6; MoTe 2